Orientasi Kewirausahaan dan Inovasi Produk pada Masa Pandemi Covid-19 terhadap Kinerja Pemasaran UMKM di Kota Tangerang - Humairoh Humairoh; Suharyadi Suharyadi; Edi Rahmat Taufik (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2021)
The Tangerang City convection MSMEs experienced a shock from a decline in demand due to economic instability caused by the Covid-19 pandemic. Tangerang City MSMEs need a survival strategy to be able to maintain their business in the midst of the Covid-19 pandemic. However, the MSMEs of Tangerang City are still experiencing obstacles in their entrepreneurial orientation and product innovation. The purpose of this study was to analyze the effect of entrepreneurial orientation and product innovation on the marketing performance of MSMEs in Tangerang City. The sample is 100 respondents. The research data was obtained by distributing questionnaires to the MSMEs business actors in Tangerang City. The data analysis technique used regression analysis with the help of SPSS software version 22. This study resulted in both partial and simultaneous entrepreneurial orientation and product innovation having a positive and significant effect on marketing performance. This study found that to improve marketing performance, business owners are responsible for finding solutions to obstacles that occur, proactively see opportunities by innovating to create new products to meet the needs of existing customers and new consumers, seek innovation ideas by listening to consumer desires and making products. that has distinctive characteristics, to continue to innovate and improve the quality of the products produced, and to increase business targets and expand product marketing so as to increase profits. The implication of this research is that MSMEs have to use online technology, namely social media and e-commerce market places in order to reach wider consumers, innovate in design and style so as to increase business profits.